2019
DOI: 10.46538/hlj.16.3.1
|View full text |Cite
|
Sign up to set email alerts
|

A Phonetic Study of Korean Heritage Learners’ Production of Korean Word-initial Stops

Abstract: The current study investigates heritage language (HL) learners’ production of the Korean three-way stop contrast. Korean consonants include a typologically rare distinction among three types of voiceless stops typically described as plain /p, t, k/, aspirated /ph, th, kh/, and tense /p*, t*, k*/. This study examines how this phonological contrast is implemented by HL learners enrolled in a beginning level Korean class at a university. Language-specific (i.e., English and Korean) gender effects in VOT are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Chang and Mandock (2019) also limited their sample to heritage learners from a single class and similarly observed relatively consistent data among speakers with less talker variability in the production of Korean stop contrasts. Thus, Chang and Mandock (2019) suggested that homogenous populations in which confounding factors are properly controlled would offer more focused and valid data suitable for the specific purpose of a study, unless the purpose of a study is to compare various characteristics of participants. Despite promising results from the present study and Chang and Mandock (2019) regarding speaker variability, it is still too early to state definitively whether using heritage subjects from a single language course can guarantee consistent results.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Chang and Mandock (2019) also limited their sample to heritage learners from a single class and similarly observed relatively consistent data among speakers with less talker variability in the production of Korean stop contrasts. Thus, Chang and Mandock (2019) suggested that homogenous populations in which confounding factors are properly controlled would offer more focused and valid data suitable for the specific purpose of a study, unless the purpose of a study is to compare various characteristics of participants. Despite promising results from the present study and Chang and Mandock (2019) regarding speaker variability, it is still too early to state definitively whether using heritage subjects from a single language course can guarantee consistent results.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, Chang and Mandock (2019) suggested that homogenous populations in which confounding factors are properly controlled would offer more focused and valid data suitable for the specific purpose of a study, unless the purpose of a study is to compare various characteristics of participants. Despite promising results from the present study and Chang and Mandock (2019) regarding speaker variability, it is still too early to state definitively whether using heritage subjects from a single language course can guarantee consistent results. Further heritage language studies in different linguistic contexts using this study design would prove instrumental in confirming the methodology’s general applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al (2011) suggested that early acquisition of fortis stops is due to the fact that only VOT needs to be mastered in order to distinguish them from the other categories. In contrast, the necessity to use F0 in order to identify lenis stops makes them acquisitionally challenging, both for L1 and L2 learners (Chang and Mandock 2019;Cheon and Lee 2013;Ko 2018;Oh et al 2010). With respect to our study, relatively late acquisition of Korean laryngeal categories, especially the lenis-aspirated contrast, and its perceptual complexity, may make this contrast more susceptible to crosslinguistic influence from the dominant language in HSs and L2 learners.…”
Section: Introductionmentioning
confidence: 71%
“…The Korean stop contrasts are typologically unusual and perceptually challenging, but at the same time sufficiently similar to the English laryngeal categories to trigger crosslinguistic interactions (Ahn et al 2017). In fact, previous research contains evidence suggestive of such crosslinguistic influence between English and Korean laryngeal categories in HSs and other types of bilinguals, both in production and perception (Chang and Mandock 2019;Cheon and Lee 2013;Cheng 2017). In the current study, we focused on the perception of word-initial lenis-aspirated distinction in Korean stops-a contrast that has already received plentiful attention in the literature but remains an attractive topic due to its uncommon phonetic implementation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation